Divergent Auto‐oxidative Alkylation and Alkanoacylation of Quinoxalin‐2(1H)‐ones with Aliphatic Aldehydes. Issue 10 (29th September 2022) - Li, Yuan; Fu, Zitong; Shen, Yawei; Zhu, Jie; Luo, Kai; Wu, Lei
Abstract: Auto‐oxidation of aliphatic aldehydes generates alkyl radicals and alkanoyl radicals, which can be intercepted to generate carbon‐carbon bonds. However, the highly reactive and unstable radical intermediates make the controlling selectivity alkylation and alkanoacylation especially challenging. Herein, we report a sustainable and controllable protocol for the auto‐oxidative alkylation and alkanoacylation of quinoxalin‐2(1 H )‐ones with good reactivity and selectivity. This protocol was presented in a green and sustainable manner, using oxygen as the only oxidant, avoiding the use of catalysts and explosive oxidants. It offers a new paradigm for a convenient, green synthesis of alkyl and alkanoyl compounds from abundant aliphatic aldehydes. Abstract : A sustainable and controllable protocol for the auto‐oxidative alkylation and alkanoacylation of quinoxalin‐2(1 H )‐ones with good reactivity and selectivity has been established. This protocol was presented in a green and sustainable manner, using oxygen as the only oxidant, avoiding the use of catalysts and explosive oxidants. It offers a new paradigm for a convenient, green synthesis of alkyl and alkanoyl compounds from abundant aliphatic aldehydes.